2016
DOI: 10.1039/c5cp07167d
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier dynamics of methylammonium lead iodide: from PbI2-rich to low-dimensional broadly emitting perovskites

Abstract: We provide an investigation of the charge carrier dynamics of the (MAI)(x)(PbI2)(1-x) system in the range x = 0.32-0.90 following the recently published "pseudobinary phase-composition processing diagram" of Song et al. (Chem. Mater., 2015, 27, 4612). The dynamics were studied using ultrafast pump-supercontinuum probe spectroscopy over the pump fluence range 2-50 μJ cm(-2), allowing for a wide variation of the initial carrier density. At high MAI excess (x = 0.90), low-dimensional perovskites (LDPs) are formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 44 publications
14
80
0
Order By: Relevance
“…15 mg·ml −1 and 20 mg·ml −1 of MAI), the size of perovskite nanocube further decreased (Figure S1h,k) and small PbI 2 peak was shown again (Figure S1g,j), which was likely due to the decomposition of MAPbI 3 29. Especially, at the highest concentration of MAI (20 mg·ml −1 ), a peak around 2 θ  = 11.5°, related to the low-dimensional perovskite structures (LDPs) such as 0D (quantum dot), 1D (chain) and 2D (sheet) structures, known to be found in MAI-rich film3031, was generated, and the performances eventually decreased to 6.8% PCE ( V oc  = 0.89 V, J sc  = 11.4 mA·cm −2 and FF  = 0.66; average values of forward and reverse scan). The performance variation of the printed PSCs according to the MAI concentration is summarized in Figure S3.…”
Section: Resultsmentioning
confidence: 91%
“…15 mg·ml −1 and 20 mg·ml −1 of MAI), the size of perovskite nanocube further decreased (Figure S1h,k) and small PbI 2 peak was shown again (Figure S1g,j), which was likely due to the decomposition of MAPbI 3 29. Especially, at the highest concentration of MAI (20 mg·ml −1 ), a peak around 2 θ  = 11.5°, related to the low-dimensional perovskite structures (LDPs) such as 0D (quantum dot), 1D (chain) and 2D (sheet) structures, known to be found in MAI-rich film3031, was generated, and the performances eventually decreased to 6.8% PCE ( V oc  = 0.89 V, J sc  = 11.4 mA·cm −2 and FF  = 0.66; average values of forward and reverse scan). The performance variation of the printed PSCs according to the MAI concentration is summarized in Figure S3.…”
Section: Resultsmentioning
confidence: 91%
“…Ultrafast UV-Vis-NIR transient absorption spectra were recorded at 920 Hz repetition frequency on three different setups employing the PSCP technique. 13,14,[24][25][26][27] In the first setup, 27,28 a multifilament Vis-NIR supercontinuum covering the wavelength range 500-920 nm was generated in a translating 2 mm thick CaF 2 plate using a noncollinearly phase-matched optical parametric amplifier (NOPA) running at 630 nm (12 mJ pulse À1 ). The NOPA was driven by a regeneratively amplified titanium:sapphire system (Spectra-Physics Hurricane, 780 nm, 90 fs, 1 mJ pulse À1 ).…”
Section: Pump -Supercontinuum Probe (Pscp) Spectroscopymentioning
confidence: 99%
“…Recent studies have shown that the remnant PbI 2 on the perovskite films passivate the defects in the grain boundaries thereby enhancing the photoconversion efficiency (PCE) of the lead‐iodide‐based hybrid perovskite solar cells . Varying the initial mole fractions of PbI 2 in methylammonium lead iodide perovskites have shown to alter the steady state absorption and the ultrafast carrier dynamics of the perovskite material . Furthermore, PbI 2 possessing the energy bandgap of 2.35 eV is a direct‐bandgap material showing high photon–electron conversion efficiency, thereby favoring its applications in efficient optoelectronic devices.…”
mentioning
confidence: 99%